A survey of availability, price, and affordability of innovative negotiated anticancer medicines: a retrospective study in Jiangsu Province, eastern China - Rui Ma; Yanyan Liu; Baolong Ding; Yuyang Sun; Hongting Yao; Man Yu; Xiaoye Wang; Lingli Zhang; Xin Li (BMC Public Health)
Abstract Background The emergence of innovative anticancer medicines has revitalized cancer treatment prospects, and improving the accessibility of innovative anticancer medicines is a key goal of national pharmaceutical policies. Despite significant efforts by the National Medical Security Administration to reform the National Reimbursement Drug List (NRDL), concerns regarding the utilization of these newly included anticancer drugs persist. This study aims to assess the accessibility of 23 Innovative Negotiated Anticancer Medicines (INAMs) in Jiangsu Province, a developed region in eastern China. Methods A retrospective survey was conducted across 319 healthcare institutions in Jiangsu Province, with 285 included for analysis. Data were obtained from procurement records of 23 INAMs. We evaluated the use of these medicines based on three aspects: availability, price measured by the defined daily dose cost (DDDc), and affordability. Results 43.5% of the 23 INAMs encountered difficulties in obtaining them, and 30.4% of 23 INAMs were very difficult to obtain. There was a notable disparity in the availability of 23 INAMs between secondary and tertiary healthcare institutions. The median DDDc for Group A and Group C showed a progressive annual reduction. The DDDc of 19 INAMs decreased during the study period, while three drugs remained unchanged, and one drug's DDDc actually increased. Family poverty caused by medicines was more pronounced among rural residents. The affordability of rural patients was significantly lower than that of urban patients (p < 0.05) in 2021 and 2022. Conclusion The accessibility of INAMs improved from 2020 to 2022. However, the accessibility of INAMs is influenced by various factors, and disparities still exist in access across different healthcare institutions and between urban and rural areas. Effective and sustainable policies need to be developed to ensure equitable access to medicines for all patients.